Relationship between school phobia and extraversion, assertiveness, and openness to experience among third-grade primary school pupils - Boudida, Leila; Mehdi, Derguini Said (The International tax journal, 2026)
School phobia represents a significant psychological challenge that may negatively affect children's academic achievement, social development, and emotional well-being. The present study aimed to investigate the relationship between school phobia and three personality traits: extraversion, assertiveness, and openness to experience among third-grade primary school pupils. A descriptive correlational design was adopted. The study sample consisted of 30 pupils (15 males and 15 females) enrolled in the third grade of primary education in the city of Constantine, Algeria. Data were collected using four questionnaires designed to measure school phobia, extraversion, assertiveness, and openness to experience. The reliability of the instruments was verified using Cronbach's alpha coefficients, which indicated satisfactory levels of internal consistency. Pearson correlation coefficients were employed to analyze the relationships among the variables. The findings revealed significant negative correlations between school phobia and extraversion (r = -0.83), school phobia and assertiveness (r = -0.90), and school phobia and openness to experience (r = -0.87). These results suggest that pupils who display lower levels of extraversion, assertiveness, and openness to experience tend to exhibit higher levels of school phobia. The study highlights the importance of considering personality characteristics in understanding and addressing school phobia among primary school children.